Application of Hypothetico-Deductive Reasoning Process for Physiotherapy Management of a Case with Meniscus Injury - Faruq Ahmed; Mohammad Rahman; Ehsanur Rahman; Shazal Das; Md. Haque (Journal of Rehabilitation Sciences and Research)
Background: Clinical reasoning refers to the professional decision-making involved in physical rehabilitation. The hypothetico-deductive reasoning (HDR) model integrates clinicians' self-perceptions with structured clinical decision-making processes. This study aimed to evaluate the application of the HDR process in the physiotherapy management of a patient with a meniscus injury.Methods: The case involved a 42-year-old male banker referred for physiotherapy rehabilitation, presenting with severe pain, swelling, catching, and locking of the right knee joint. This single-case study was addressed using the HDR process.Results: By the eighth week of intervention, improvements were observed in pain reduction, muscle strength, and range of motion of the knee joint. Additionally, the meniscus evaluation score improved from 20.9% to 71.4%. The subject is now able to participate in routine daily activities. Clinical reasoning, central to practice, was critical in this atypical presentation of a meniscus tear; thus, the HDR process was employed for diagnosis and problem-solving.Conclusion: The HDR process offers a holistic treatment framework and can be effectively applied to unfamiliar or atypical clinical conditions such as meniscus injuries.